Characterization and Description of Friction Conditions for Hot Stamping and Partial Hot Stamping of Ultra High Strength Steel - Schwingenschlögl, Patrik; Hildering, Sven; Merklein, Marion (Proceedings METEC & 2nd ESTAD, 2015)
LFT Import::2019-08-05 (2104)

Characterization of tribological conditions within direct hot stamping - Schwingenschlögl, Patrik; Merklein, Marion (Journal of Materials Processing Technology, 2020)
The aim of this study is to create a detailed process understanding regarding the tribological conditions within direct hot stamping. Hot stamping has established as a common technology for manufacturing safety-relevant components in modern car bodies. However, due to the high forming temperatures within hot stamping applications, no suitable lubricants have been developed yet. As a consequence, high friction and severe wear occur during the forming. This affects the tool wear as well as the resulting part quality. For improving the robustness and the efficiency of industrial hot stamping processes, future measures to reduce the tribological loads have to be found. The key to the development of such measures is a detailed process understanding of the tribological conditions. Within this study, friction and wear are analyzed for different workpiece and tool temperatures, relative velocities and contact pressures. Based on the experimental results, detailed knowledge of the critical cause-effect relations between process parameters and tribological behavior is acquired. The friction behavior is analyzed via strip drawing experiments under hot stamping conditions. The amount of wear is determined via confocal microscopy measurements before and after the experiments. The results of this study help to improve the process understanding of the tribological conditions within the hot stamping process and to develop future measures for reducing tool wear.
CRIS-Team Scopus Importer:2019-12-17
Keywords: 22MnB5; AlSi; Friction; Hot stamping; Strip drawing test; Wear

Einfluss der Werkzeugeigenschaften auf die tribologischen Bedingungen beim Presshärten - Schwingenschlögl, Patrik; Merklein, Marion (XXXVII. Verformungskundliches Kolloquium, 2018)
LFT Import::2019-08-05 (2311)

Einfluss der Werkzeugtemperatur auf die tribologischen Bedingungen beim Presshärten - Schwingenschlögl, Patrik; Tenner, Jennifer; Gauglitz, S.; Merklein, Marion (11. Erlanger Workshop Warmblechumformung, 2016)
LFT Import::2019-08-05 (2217)

Erarbeitung eines Prozessverständnisses zur Verbesserung der tribologischen Bedingungen beim Presshärten - Schwingenschlögl, Patrik (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
With the growing numbers of automobiles in Germany, the demands of modern passenger cars regarding safety and efficiency constantly increase. The application of hot stamped parts allows reducing the weight of the body in white and simultaneously improving passenger safety. However, high forming temperatures prevent the use of lubricants, so that high friction and tool wear limit the process window. In order to use the full potential of the hot stamping process, the development of measures to reduce friction and wear is needed. For this purpose, a method for characterizing the tribological conditions within hot stamping has been elaborated within this work. This method allows for analyzing the friction and wear conditions reproducible and specifically. With this method, a comprehensive process understanding regarding the predominant tribological conditions has been created. Based on the created process understanding tool-side measures for reducing friction and wear have been identified. The experimental investigations indicate that the choice, as well as the heat treatment of the tool material and the application of PVD-tool-coatings, can reduce friction and wear. Concluding, the transferability of the findings of the strip drawing tests on a B-pillar-geometry in laboratory-scale was shown. Thus, it can be concluded that the basic findings of this work can be used for hot stamping processe

Investigation of Friction Conditions at Elevated Temperatures for Hot Stamping - Schwingenschlögl, Patrik; Hildering, Sven; Merklein, Marion (Proceedings 7th International Conference on Tribology in Manufacturing Processes, 2016)
LFT Import::2019-08-05 (2162)

Investigation of the influence of process parameters on adhesive wear under hot stamping conditions - Schwingenschlögl, Patrik; Weldi, Maraike; Merklein, Marion (Journal of Physics: Conference Series, 2017)
LFT Import::2019-08-05 (2236)

Investigation of Tribological Conditions within Partial Hot Stamping - Schwingenschlögl, Patrik; Steiner, Jennifer; Andreas, Kolja; Merklein, Marion (Hot Sheet Metal Forming of high-Performance Steel - CHS2, 2017)
The importance of lightweight construction in modem car bodies is motivated by current challenges like reducing the fuel consumption and increasing safety standards. Besides the substitution of common steel grades with aluminum alloys and high strength steels, hot stamping has been established for producing safety relevant components. By using hot stamped parts, the fuel consumption can be reduced while improving the crash performance due to the substitution of conventional steel grades by hot stamped high strength steels with thinner sheet thickness. Partial hot stamping represents a variation of direct hot stamping and provides the opportunity of adjusting the final mechanical properties by altering the tool temperature. Thus, the passenger safety can be further improved by producing structural components with tailored properties considering the final requirements. Finite-element (FE) simulation plays an important role for the design of partial hot stamping processes due to thermo-mechanical interdependences taking place during the forming. In order to achieve an accurate modelling of the process, reliable input parameters are necessary. Currently, hot stamping processes are modelled assuming a constant friction coefficient due to the knowledge gap regarding the tribological behavior within hot stamping. For the experimental investigation of the tribological conditions under direct hot stamping conditions, a hot strip drawing test rig is used within this study. The influence of tool temperature on the friction is examined for varied workpiece temperatures, contact pressures and drawing velocities. The experiments are performed with AISi coated 22MnB5. For analyzing friction and wear mechanisms, the surfaces of the specimens are characterized.
LFT Import::2019-08-05 (2234)

Investigation on basic friction and wear mechanisms within hot stamping considering the influence of tool steel and hardness - Schwingenschlögl, Patrik; Niederhofer, Philipp; Merklein, Marion (Wear, 2019)
Hot stamping is a well-established technology for producing safety relevant car components. The use of hot stamped components in modern car bodies offers the possibility of improving crash performance due to their high strength while simultaneously decreasing the fuel consumption by reducing sheet thicknesses and thus weight. Hot stamped components are mainly produced using the boron-manganese-alloyed steel 22MnB5. To prevent formation of oxide layer during heat treatment and subsequent forming process, AlSi-coatings are applied on the workpiece surface. Since hot stamped parts are formed at temperatures between 600 degrees C and 800 degrees C, no suitable lubricants have been found yet. Thus, severe wear and high friction occur during the forming process affecting final part quality as well as life-time of hot stamping tools. Consequently, measures for reducing tribological load during the forming operation have to be found in order to improve part quality and increase efficiency of industrial hot stamping applications. Within this study, the impact of the tool material on friction and wear is analyzed by comparing the tribological behavior of the newly developed high thermal conductivity hot work tool steel Thermodur 2383 Supercool with the reference material 1.2367. Both are characterized by means of flat strip drawing experiments under hot stamping conditions. The experiments are performed with different hardness values for each of the two tool materials. Furthermore, wear behavior is analyzed using scanning electron microscope and confocal microscope measurements of workpiece and tool. Hereby, fundamental wear and friction mechanisms within hot stamping applications are identified. The results of this study help to increase the process understanding regarding the tribological conditions during hot stamping. In future research work tool-side measures for increasing the life-time of hot stamping tools will be developed.
CRIS-Team WoS Importer:2019-04-30

Properties of Tool Steels for Application in Hot Stamping - Niederhofer, Philipp; Eger, Kathrin; Schwingenschlögl, Patrik; Merklein, Marion (Steel Research International, 2019)
Hot stamped high-strength steel components for car bodies become increasingly important due to the need to save weight for multiple reasons such as fuel conservation regulations. Tribological systems in tools for hot stamping depend on process parameters and may include, e.g., mechanical and thermal loads as well as adhesive and abrasive wear. Furthermore, the process cycle time should be as short as possible due to economic reasons. Commonly used hot work tool steels mainly suffer from rather low wear resistance, whereas in terms of process cycle time, a high thermal conductivity is desired. Thus, solutions showing optimized combination of key properties for application in hot stamping such as wear resistance, high thermal conductivity, toughness, and hardening behavior need to be found. In this contribution, novel high thermal conductivity hot work tool steels, especially designed for application in hot stamping, are presented and some key properties are compared, e.g., to those of conventional hot work tool steels like 1.2367, which is commonly used in this application. Furthermore, tribological investigations are performed in laboratory tests according to ASTM G65 and G75 as well as a flat strip-drawing test setup using sheets of 22MnB5 under hot stamping conditions.
CRIS-Team WoS Importer:2019-12-10

Tribological Behavior of Different Tool Steels and Surface Properties under Hot Stamping Conditions - Schwingenschlögl, Patrik; Tenner, Jennifer; Merklein, Marion (Key Engineering Material, 767, 2018)
LFT Import::2019-08-05 (2313)
Keywords: 22MnB5; Friction; Hot stamping; Tool steel; Wear

Tribological behavior of Zn coated 22MnB5 in hot stamping - Schwingenschlögl, Patrik; Tenner, Jennifer; Andreas, Kolja; Merklein, Marion (Steels in Cars and Trucks, 2017)
LFT Import::2019-08-05 (2235)

Tribological challenges in press hardening - Schwingenschlögl, Patrik; Merklein, Marion (Stahl und Eisen, 2019)
Hot stamping has established as a common technology for manufacturing safety-relevant components in modern vehicle bodies. By applying thin sheet thicknesses, using hot stamped parts offers the chance of improving crash performance while towering the mileage. The most commonly used material for hot stamped components is the high-strength-steel 22MnB5. In order to avoid the formation of oxide scale during the heat treatment and the subsequent forming process, an AISi coating is applied to the boron-manganese-steel. Due to the forming temperatures between 600 °C and 850 °C, no suitable lubricants have been found yet. Thus, high friction and severe wear occur during the forming. This has an impact on the resulting part quality as well as the tool lifetime. As a consequence, future measures that reduce the tribological loads have to be found in order to improve the robustness and the efficiency of industrial hot stamping applications. Within this study, friction and wear are characterized for different workpiece and tool temperatures, relative velocities and contact pressures. Based on the experimental results, suggestions regarding the process design of hot stamping applications will be given.
CRIS-Team Scopus Importer:2021-04-20

Untersuchung der Reibbedingungen beim Presshärten mittels Streifenziehversuchen bei erhöhten Temperaturen - Schwingenschlögl, Patrik; Hildering, Sven; Merklein, Marion (10. Erlanger Workshop Warmblechumformung, 2015)
LFT Import::2019-08-05 (2129)

Werkzeugseitige Beeinflussung der tribologischen Bedingungen beim Presshärten - Schwingenschlögl, Patrik; Hauser, D.; Tenner, Jennifer; Merklein, Marion (Tagungsband zum 12. Erlanger Workshop Warmblechumformung, 2017)
LFT Import::2019-08-05 (2275)